Problems of massive open online distance learning courses in distance learning systems - V. M. Kukharenko (Academy of Cognitive and Natural Sciences, 2013)
The term "Massive Open Distance Learning" was coined by George Siemens in 2008. The process of learning in such courses is the process of creating a network whose nodes are external entities (people, organizations, libraries, websites, books, magazines, databases, or any other source of information). The act of learning consists in the creation of an external network of nodes. In recent years there have been several dozens of open online courses, which have been called cMOOS ( massive open online courses) and are based on a new approach, which has been called connectivism.